2009
DOI: 10.1097/tp.0b013e3181aa8f62
|View full text |Cite
|
Sign up to set email alerts
|

Sustained BK Viruria as an Early Marker for the Development of BKV-Associated Nephropathy: Analysis of 4128 Urine and Serum Samples

Abstract: Sustained BK viruria is a reliable marker allowing an early identification of patients at high risk of BKVAN development and therefore assure precocious therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
65
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 17 publications
9
65
1
1
Order By: Relevance
“…Our data on BKV dynamics support the existing literature, as urine and plasma BK viral loads at BKVN diagnosis were comparable to levels reported in the literature (1,15). In addition, patients who developed viremia had higher levels of virus in their urine and urine viral loads were always higher than those in the plasma (16).…”
Section: Discussionsupporting
confidence: 79%
“…Our data on BKV dynamics support the existing literature, as urine and plasma BK viral loads at BKVN diagnosis were comparable to levels reported in the literature (1,15). In addition, patients who developed viremia had higher levels of virus in their urine and urine viral loads were always higher than those in the plasma (16).…”
Section: Discussionsupporting
confidence: 79%
“…In the first year after transplantation, 10%-20% of kidney transplant recipients develop BK viremia. Reduction of immunosuppression is the mainstay of therapy (4). With aggressive surveillance protocols, aimed to detect viremia before the development of impaired kidney function, graft loss now occurs in less than 5% of viremic patients.…”
Section: Discussion Of Case 1 (Question 1a)mentioning
confidence: 99%
“…In our studies using BKV VP1 mRNA levels, we found the incidence of BKV replication to be 10% at 1 month, 20% at 3 months, 30% at 6 months which plateaued at 12 month post-transplantation. Similarly other studies identified viruria rates of 19% to 49% within the first year post-transplantation using DNA based assays [9,10]. Hirsch and colleagues detected BKV replication using decoy cells in the urine in 30% of their study population [11].…”
Section: Natural History Of Bkv Replicationmentioning
confidence: 99%